Die Wirksamkeit verschiedener Lehramtsstudiengänge Physik im Vergleich - Riese, Josef; Reinhold, Peter (Naturwissenschaftliche Bildung als Beitrag zur Gestaltung partizipativer Demokratie. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Potsdam 2010)

Quereinsteiger in das Lehramt Physik in der Sekundarstufe 1 - Oettinghaus, Lars; Korneck, Friederike; Lamprecht, Jan; Riese, Josef (PhyDid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung 2011 in Münster)

Unterschiede im Professionswissen bei angehenden Physiklehrkräften – Ein Vergleich verschiedener Lehramtszugänge - Riese, Josef; Gramzow, Yvonne; Reinhold, Peter; Oettinghaus, Lars; Korneck, Friederike (PhyDid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung 2011 in Münster)

Wissensbasierte Kompetenzprofile angehender Physiklehrkräfte - Gramzow, Yvonne; Riese, Josef; Reinhold, Peter (PhyDid A - Physik und Didaktik in Schule und Hochschule)
Um die Qualität der Ausbildung von Lehrkräften beurteilen zu können, wurden in den letzten Jahren verschiedene Untersuchungen zur Kompetenzmodellierung und Kompetenzmessung bei Lehramtsstudierenden und Lehrkräften initiiert. Im Zusammenhang mit möglichen Maßnahmen zur Verbesserung der Lehrerausbildung wird dabei auch über bedarfsgerechte und individualisierte Fördermaßnahmen gesprochen. Als erster Schritt auf diesem Weg kann eine Typenbildung in der Gruppe der Lehramtsanwärter dazu dienen, eine gezielte Binnendifferenzierung vorzunehmen. Vor diesem Hintergrund wurden in der vorgestellten Analyse die Daten einer bundeslandübergreifenden Kompetenzmessung bei Lehramtsstudierenden der Physik dazu genutzt, eine Typisierung auf der Grundlage der gemessenen Leistungen in den drei Bereichen des Professionswissens von Physiklehrkräften (Fachwissen, fachdidaktisches Wissen, allgemeines pädagogisches Wissen) durchzuführen. Dabei konnten drei unterschiedliche Kompetenzprofile identifiziert werden: ein fachenthusiastisches Profil, ein schulpraktisch orientiertes Profil und ein leistungsschwaches Profil. Die identifizierten Profile werden im Weiteren anhand demographischer Daten, Beliefs und motivationaler Orientierungen charakterisiert, so dass die Ergebnisse als Anknüpfungspunkt genutzt werden könnten, um künftig eine stärkere Individualisierung der Lehrerausbildung speziell im Fach Physik zu realisieren.

Freies Spiel beobachten. Chancen und Stolpersteine - Bruns, Julia; Eichen, L.; Pfiffner, M.; Walter-Laager, C. (gruppe & spiel)

Geschlechterforschung. Theorien, Thesen und Themen zur Einführung.
Das Studienbuch gibt einen einführenden Überblick zum Stand der Geschlechterforschung in verschiedenen Disziplinen. Es eröffnet grundlegende Einblicke zum aktuellen Stand der Diskussion, erörtert zentrale und spezifische Fragestellungen und folgt der Geschichte der Geschlechterdebatte in den verschiedenen wissenschaftlichen Fächern. Dabei finden neben den Sozial- und Geisteswissenschaften auch die Natur- und Technikwissenschaften ausführliche Berücksichtigung. Das Buch erschöpft sich dabei nicht in einer Bestandsaufnahme, sondern greift beispielhaft aktuelle Forschungs- und Fragestellungen auf, die ein Licht werfen auf die beeindruckende Themenvielfalt, die ergebnisreichen Einsichten, aber auch die zukünftigen Aufgaben der Geschlechterforschung. Das Glossar am Ende des Bandes erläutert die wichtigsten Begriffe aus dem Bereich der Geschlechterforschung und verweist auf hilfreiche weiterführende Literatur.

Jungenpädagogik im Widerstreit
Seit längerem wird in der pädagogischen Fachliteratur der Befund diskutiert, dass Mädchen im Bildungssystem erfolgreicher sind als Jungen. Wie ist dieses Phänomen zu erklären? Hat die Pädagogik die Grenzen und Unterschiede zwischen den Geschlechtern unterschätzt? Die Debatte über Jungen und ihre Probleme ist von einer stark vereinfachenden Gewinn-Verlust-Rechnung und einer dramatisierenden Tonlage gekennzeichnet, die die Komplexität des Themas eher verdecken als aufzuklären vermögen. Ziel des Buches ist es, aus unterschiedlichen Blickwinkeln den aktuellen internationalen Forschungsstand und die thematischen Brennpunkte der aktuellen Jungendebatte zu erörtern. Daraus werden schließlich Perspektiven für eine kritische Pädagogik der Geschlechter für Jungen und Mädchen entwickelt.

Intercultural Competence among Sports and PE Teachers. Theoretical Foundations and Empirical Verification - Grimminger-Seidensticker, Elke (European Journal of Teacher Education)

Zum Umgang mit Heterogenität im Sportunterricht. Die Bedeutsamkeit von Genderkompetenz und Interkultureller Kompetenz von Sportlehrkräften - Grimminger-Seidensticker, Elke; Frohn, J. (Empirie des Schulsports: Forschungsstand und Befunde)

Die Erfahrung von Anerkennung und Zugehörigkeit im Schulsport. Empirische Befunde und sportpädagogische Differenzierungen - Grimminger-Seidensticker, Elke; Gieß-Stüber, P. (Sportpädagogik als Erfahrungswissenschaft)

Anerkennungs- und Missachtungskulturen von Mädchen und Jungen im Sportunterricht - Grimminger-Seidensticker, Elke (Geschlecht und bewegungsbezogene Bildung(sforschung))

Application of the Discontinuous Galerkin Time Domain Method to the Optics of Bi-Chiral Plasmonic Crystals - Grynko, Yevgen; Förstner, Jens; Meier, Torsten; Radke, André; Gissibl, Timo; Braun, Paul V.; Giessen, Harald
A simulation environment for metallic nanostructures based on the Discontinuous Galerkin Time Domain method is presented. It is used to model optical transmission by silver bi‐chiral plasmonic crystals. The results of simulations qualitatively and quantitavely agree with experimental measurements of transmitted circular polarization.
Keywords: tet_topic_meta

Virtual tester development using HDL/PLI - Kamran, Arezoo; Nemati, Nastaran; Sadeghi-Kohan, Somayeh; Navabi, Zainalabedin (2010 East-West Design & Test Symposium (EWDTS))

Synthesis of highly stable magnesium fluoride suspensions and their application in the corrosion protection of a Magnesium alloy - Waltz, Florian; Swider, Mark A.; Hoyer, Kay-Peter; Hassel, Thomas; Erne, Martin; Möhwald, Kai; Adlung, Matthias; Feldhoff, Armin; Wickleder, Claudia; Bach, Friedrich-Wilhelm; Behrens, Peter (Journal of Materials Science)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

The ‘German Nation’ and the ‘black Other’: Social Darwinism and the cultural mission in German colonial discourse - Schubert, Michael (Patterns of Prejudice)

French, Belgian, British and US Occupation Troops in Western and Southwestern Germany 1918-1930 - Schubert, Michael (The Encyclopedia of Migration and Minorities in Europe. From the 17th Century to the Present)

(the ActiFE Study Group). Walking on sunshine: effect of weather conditions on physical activity in older people - Klenk, J.; Büchele, G.; Rapp, K.; Franke, Sebastian; Peter, R. (Journal of Epidemiology and Community Health. JECH Online First, published on February 15, 2011)

Assessing the long-term effect of industrial services on firm profitability: The moderating impact of product innovations (ausgezeichnet mit Best Overall Conference Paper Award) - Eggert, A.; Hogreve, J.; Ulaga, W.; Münkhoff, Eva (2011 AMA Winter Academic Conference, Austin, TX)

Service orientation of manufacturing companies: A necessary or sufficient condition for firm profitability? - Eggert, A.; Münkhoff, Eva; Thiesbrummel, C. (40th EMAC Annual Conference, Ljubljana)

Time extension of sales promotions – How do customers react? - Münkhoff, Eva; Garnefeld, I.; Bruns, A. (40th EMAC Annual Conference, Ljubljana)

Industrial services, product innovations, and firm profitability: A multiple-group latent growth curve analysis - Eggert, Andreas; Hogreve, Jens; Ulaga, Wolfgang; Münkhoff, Eva (Industrial Marketing Management)
Keywords: Marketing

Die unbewusste Wahrnehmung einer Wurftäuschung im Handball - Güldenpenning, Iris; Machlitt, Daniel; Schack, Thomas (Abstracts of the 53nd Conference of Experimental Psychologists (TeaP))

Die Rolle motorischer Expertise in der Bewegungswahrnehmung: Eine EEG-Studie - Koester, Dirk; Güldenpenning, Iris; Schack, Thomas (Abstracts of the 53nd Conference of Experimental Psychologists (TeaP))

Experimentelle Untersuchungen zur zeitlichen Ordnung mentaler Repräsentationen - Güldenpenning, Iris; Koester, Dirk; Schack, Thomas (Embodiment: Wahrnehmung-Kognition-Handlung. Tagung der dvs-Sektion Sportmotorik)

Bewegungspriming des Angriffsverhaltens im Volleyball - Frantzen, Christian; Güldenpenning, Iris; Schack, Thomas (Embodiment: Wahrnehmung-Kognition-Handlung. Tagung der dvs-Sektion Sportmotorik)

Wahrnehmung einer Täuschungshandlung im Beachvolleyball - Steinke, A; Güldenpenning, Iris; Schack, Thomas (Embodiment: Wahrnehmung-Kognition-Handlung. Tagung der dvs-Sektion Sportmotorik)

Erkennen von Finten auf Grundlage unbewusster Reize? - Machlitt, Daniel; Güldenpenning, Iris; Schack, Thomas (Embodiment: Wahrnehmung-Kognition-Handlung. Tagung der dvs-Sektion Sportmotorik)

Verarbeitung komplexer Bewegungen: Eine EEG-Studie - Koester, Dirk; Güldenpenning, Iris; Schack, Thomas (Embodiment: Wahrnehmung-Kognition-Handlung. Tagung der dvs-Sektion Sportmotorik)

Chunking and categorization in motor memory? Experimental studies in free climbing - Schack, Thomas; Güldenpenning, Iris (Sport and Exercise Psychology: Human Performance, Well-being and Health: Proceedings of the 13th FEPSAC European Congress of Sport Psychology)

Motor expertise modulates the unconscious processing of human body postures - Güldenpenning, Iris; Koester, Dirk; Kunde, Wilfried; Weigelt, Matthias; Schack, Thomas (Experimental Brain Research)

Neurophysiologische Korrelate der Wahrnehmungs-Handlungs-Kopplung am Beispiel des leichtathletischen Hochsprungs - Koester, D.; Güldenpenning, Iris; Schack, T. (Kreativität – Innovation – Leistung. 20. dvs- Hochschultag)

Effekte einer Jonglierintervention auf die kognitive Leistung und die Gehirnaktivität von Grundschülern - Koutsandreou, F; Reinecke, K; Schade, J; Cordes, M; Schubert, M; Kehne, Miriam; Kämpfe, A; Baumeister, Jochen (Kreativität - Innovation - Leistung)

Studium heute: gesundheitsfördernd oder -gefährdend?: eine Lebensstilanalyse. Dokumentation 16. bundesweiter Kongress Armut und Gesundheit: 3./4. Dezember 2010 in Berlin - Brandl-Bredenbeck, Hans-Peter; Köster, Carolin; Kämpfe, Astrid

Transformation of scientific algorithms to parallel computing code: subdomain support in a MPI-multi-GPU backend - Meyer, Björn; Plessl, Christian; Förstner, Jens (Symp. on Application Accelerators in High Performance Computing (SAAHPC))
Keywords: tet_topic_hpc

Cooperative multitasking for heterogeneous accelerators in the Linux Completely Fair Scheduler - Beisel, Tobias; Wiersema, Tobias; Plessl, Christian; Brinkmann, André (Proc. Int. Conf. on Application-Specific Systems, Architectures, and Processors (ASAP))

Measuring and Predicting Temperature Distributions on FPGAs at Run-Time - Happe, Markus; Agne, Andreas; Plessl, Christian (Proceedings of the 2011 International Conference on Reconfigurable Computing and FPGAs (ReConFig))
In the next decades, hybrid multi-cores will be the predominant architecture for reconfigurable FPGA-based systems. Temperature-aware thread mapping strategies are key for providing dependability in such systems. These strategies rely on measuring the temperature distribution and redicting the thermal behavior of the system when there are changes to the hardware and software running on the FPGA. While there are a number of tools that use thermal models to predict temperature distributions at design time, these tools lack the flexibility to autonomously adjust to changing FPGA configurations. To address this problem we propose a temperature-aware system that empowers FPGA-based reconfigurable multi-cores to autonomously predict the on-chip temperature distribution for pro-active thread remapping. Our system obtains temperature measurements through a self-calibrating grid of sensors and uses area constrained heat-generating circuits in order to generate spatial and temporal temperature gradients. The generated temperature variations are then used to learn the free parameters of the system's thermal model. The system thus acquires an understanding of its own thermal characteristics. We implemented an FPGA system containing a net of 144 temperature sensors on a Xilinx Virtex-6 LX240T FPGA that is aware of its thermal model. Finally, we show that the temperature predictions vary less than 0.72 degree C on average compared to the measured temperature distributions at run-time.

Performance Estimation Framework for Automated Exploration of CPU-Accelerator Architectures - Kenter, Tobias; Platzner, Marco; Plessl, Christian; Kauschke, Michael (Proc. Int. Symp. on Field-Programmable Gate Arrays (FPGA))
Keywords: design space exploration; LLVM; partitioning; performance; estimation; funding-intel

FPGA Acceleration of Communication-bound Streaming Applications: Architecture Modeling and a 3D Image Compositing Case Study - Schumacher, Tobias; Süß, Tim; Plessl, Christian; Platzner, Marco (Int. Journal of Recon- figurable Computing (IJRC))
Keywords: funding-altera

Just-in-time Instruction Set Extension – Feasibility and Limitations for an FPGA-based Reconfigurable ASIP Architecture - Grad, Mariusz; Plessl, Christian (Proc. Reconfigurable Architectures Workshop (RAW))

Measuring physical activity of children - Development of a new self-report questionaire - Kämpfe, Astrid; Kehne, Miriam (Moving People, Moving Forward)

Walking Bus - der aktive Schulweg - Kehne, Miriam (Schulverwltung - Zeitschrift für Schulleitung und Schulaufsicht)

Zur Wirkung von Alltagsaktivität auf kognitive Leistungen von Kindern. Eine empirische Untersuchung am Beispiel des aktiven Schulwegs - Kehne, Miriam

E-Mentoren bei der Virtual Science Fair – eine innovative Facette in der Lehrerausbildung - Jonas-Ahrend, Gabriela (Journal Hochschuldidaktik)

Selbstbeschreibung – Pamir/Massenmedien - Bartz, Christina (Systemtheoretische Literaturwissenschaft. Begriffe – Methoden – Anwendungen)

Die Magie des Augenblicks. Echtzeitmedium Fernsehen - Bartz, Christina (The European (23.09.11))

Selbstbeschreibung – Pamir / Massenmedien - Bartz, Christina (Systemtheoretische Literaturwissenschaft. Begriffe – Methoden – Anwendungen)

Anti-phase domains in cubic GaN - Maria Kemper, Ricarda; Schupp, Thorsten; Häberlen, Maik; Niendorf, Thomas; Maier, Hans-Jürgen; Dempewolf, Anja; Bertram, Frank; Christen, Jürgen; Kirste, Ronny; Hoffmann, Axel; Lindner, Jörg; As, Donat (Journal of Applied Physics)
The existence of anti-phase domains in cubic GaN grown on 3C-SiC/Si (001) substrates by plasma-assisted molecular beam epitaxy is reported. The influence of the 3C-SiC/Si (001) substrate morphology is studied with emphasis on the anti-phase domains (APDs). The GaN nucleation is governed by the APDs of the substrate, resulting in equal plane orientation and the same anti-phase boundaries. The presence of the APDs is independent of the GaN layer thickness. Atomic force microscopy surface analysis indicates lateral growth anisotropy of GaN facets in dependence of the APD orientation. This anisotropy can be linked to Ga and N face types of the {111} planes, similar to observations of anisotropic growth in 3C-SiC. In contrast to 3C-SiC, however, a difference in GaN phase composition for the two types of APDs can be measured by electron backscatter diffraction, μ-Raman and cathodoluminescence spectroscopy.

Pop, Populäres und Theorien. Forschungsansätze und Perspektiven zu einem prekären Verhältnis in der Medienkulturgesellschaft

Pattern-Based Modeling and Formalizing of Business Process Quality Constraints - Khaluf, Lial; Gerth, Christian; Engels, Gregor

Unsupervised learning of acoustic events using dynamic time warping and hierarchical K-means++ clustering - Schmalenstroeer, Joerg; Bartek, Markus; Haeb-Umbach, Reinhold (Interspeech 2011)
In this paper we propose to jointly consider Segmental Dynamic Time Warping and distance clustering for the unsupervised learning of acoustic events. As a result, the computational complexity increases only linearly with the dababase size compared to a quadratic increase in a sequential setup, where all pairwise SDTW distances between segments are computed prior to clustering. Further, we discuss options for seed value selection for clustering and show that drawing seeds with a probability proportional to the distance from the already drawn seeds, known as K-means++ clustering, results in a significantly higher probability of finding representatives of each of the underlying classes, compared to the commonly used draws from a uniform distribution. Experiments are performed on an acoustic event classification and an isolated digit recognition task, where on the latter the final word accuracy approaches that of supervised training.